2015
DOI: 10.1016/j.provac.2015.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Use of Yeast Lysate in Women with Recurrent Vulvovaginal Candidiasis

Abstract: Vulvovaginal candidiasis (VVC) affects a significant number of women, especially in working age. In an estimated 75% of women an episode of acute vulvovaginal candidiasis occurs during lifetime and another 5 -10% of women develop recurrent vulvovaginal candidiasis (RVVC). This is mainly characterized by intense burning, itching, pain, abnormal discharge, dyspareunia. Immune response to candidiasis is both cellular (CMI) (natural protection mechanisms) and humoral (antibody production). Understanding the princi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…In addition to their predominant use in the treatment of respiratory tract disorders like asthma, COPD and rhinitis, bacterial lysates have shown encouraging results in the treatment of various diseases like diverticulitis, rheumatoid arthritis, type 1 diabetes, inflammatory bowel disease, urinary tract infections, periodontitis, relapse of tuberculosis and food allergy [16][17][18][19][20][21][22]. Bacterial lysates are also effective against fungal and viral infections [23][24][25][26]. Interestingly, fungal lysates like bacterial lysates contain many immunogenic proteins, though a few studies on their role as immunostimulants have been reported so far [23,24,27].…”
Section: What Are Microbial Lysates and How Are They Related To The M...mentioning
confidence: 99%
See 3 more Smart Citations
“…In addition to their predominant use in the treatment of respiratory tract disorders like asthma, COPD and rhinitis, bacterial lysates have shown encouraging results in the treatment of various diseases like diverticulitis, rheumatoid arthritis, type 1 diabetes, inflammatory bowel disease, urinary tract infections, periodontitis, relapse of tuberculosis and food allergy [16][17][18][19][20][21][22]. Bacterial lysates are also effective against fungal and viral infections [23][24][25][26]. Interestingly, fungal lysates like bacterial lysates contain many immunogenic proteins, though a few studies on their role as immunostimulants have been reported so far [23,24,27].…”
Section: What Are Microbial Lysates and How Are They Related To The M...mentioning
confidence: 99%
“…Bacterial lysates are also effective against fungal and viral infections [23][24][25][26]. Interestingly, fungal lysates like bacterial lysates contain many immunogenic proteins, though a few studies on their role as immunostimulants have been reported so far [23,24,27].…”
Section: What Are Microbial Lysates and How Are They Related To The M...mentioning
confidence: 99%
See 2 more Smart Citations
“…The authors showed that live yeast and βglucans were able to modulate the immune system by promoting cell viability, phagocytic activity, antioxidant immune response, immune-related gene expression, and induction of trained immunity in goat peripheral blood leukocytes and newborn goats (Medina-Córdova et al, 2018;Angulo et al, 2018;Angulo et al, 2019;Angulo et al, 2020). Remarkably, Vrzal et al (2015) reported that administrating a patented commercial immunostimulant product based on Candida albicans, C. krusei, C. glabrata, and Propionibacterium acnes lysates prolonged the relapse period of vulvovaginal affections and had a positive effect on cellular immunity qualities in women. Therefore, this study was designed to evaluate the immunostimulant activity of lysates derived from five marine yeast D. hansenii strains in goat peripheral blood leukocytes using in vitro assays.…”
Section: Introductionmentioning
confidence: 99%